World Oil Price and Biofuels A General Equilibrium Analysis - Timilsina, Govinda R. (The World Bank, 2011)
The price of oil could play a significant role in influencing the expansion of biofuels. However, this issue has not been fully investigated yet in the literature. Using a global computable general equilibrium model, this study analyzes the impact of oil price on biofuel expansion, and subsequently, on food supply. The study shows that a 65 percent increase in oil price in 2020 from the 2009 level would increase the global biofuel penetration to 5.4 percent in 2020 from 2.4 percent in 2009. A doubling of oil price in 2020 from its baseline level, or a 230 percent increase from the 2009 level, would increase the global biofuel penetration in 2020 to 12.6 percent. The penetration of biofuels is highly sensitive to the substitution possibility between biofuels and their fossil fuel counterparts. The study also shows that aggregate agricultural output drops due to an oil price increase, but the drop is small in major biofuel producing countries as the expansion of biofuels would partially offset the negative impacts of the oil price increase on agricultural outputs. An increase in oil price would reduce global food supply through direct impacts as well as through diversion of food commodities and cropland toward the production of biofuels